Pengembangan Sosial pada Anak Usia 5-6 Tahun dan Keterlibatan Orang Tua di TK Q Baiturrahman - Ihsania Torfi Rangkuti; Kasuma Hian Hasibuan; Adenia Adenia; Nabila Ulfa Khairiyah; Khadijah Khadijah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to explore the socio-emotional development of children aged 5–6 years at TKQ Baiturrahman and to analyze the involvement of the school and parents in supporting this development. Using a descriptive qualitative approach, data were collected through observation and interviews. The results show that most children have developed as expected in aspects such as empathy, social affiliation, conflict resolution, and positive habits. However, some children still require further guidance in understanding others' emotions and resolving conflicts peacefully. These findings align with the theories of Erikson, Goleman, and Wolfinger, emphasizing the importance of developing empathy, self-awareness, and social responsibility. The study recommends active collaboration between teachers and parents to foster a supportive environment for optimal socio-emotional development.